Otimização da preparação de eletrodo de pasta de carbono contendo riboflavina imobilizada em suporte inorgânico - Pereira,Arnaldo César (2004)
The aim of this work was to optimize the preparation of electrodes with riboflavin (RF) immobilized on a silica surface modified with niobium oxide and carbon paste. Electrode preparation was optimized employing a factorial design consisting of two levels and three factors. The electrochemical properties of immobilized RF were investigated by cyclic voltammetry. The factorial analysis was carried out analysing the current intensity (Ipa). It was possible to optimize the electrode to get the best reversibility in the redox process, i. e. the lowest separation between anodic and cathodic peak potentials and a current ratio close to unity. The concentration of supporting electrolyte has a small effect. The proportion has the highest effect and the interaction factor between proportion and mixture has also a significant effect on the current intensity.